YHWH in a Suit: Kəbôd YHWH as the Regalia of the Priestly God - Bae, Sun Bok (Journal for the study of the Old Testament, 2023)
Kāḇôḏ in kəḇôḏ YHWH has been translated predominantly with abstract words such as “glory” or “presence” throughout the Hebrew Bible. Some scholars argue that kəḇôḏ YHWH simultaneously marks the divine presence and hides the divine essence. These understandings do not capture the specific function and signification of kəḇôḏ YHWH in the pentateuchal Priestly source (P and H). In P and H, kəḇôḏ YHWH conveys the imagery of radiant, fiery clothing, comparable to Mesopotamian melammu. The deity always appears before the public with kəḇôḏ YHWH, whereas the text never says that the deity meets anyone privately with it. kəḇôḏ YHWH expresses the royal aspect of the deity who requires honor and submission. This understanding of kəḇôḏ YHWH in P reveals that the Priestly God is not abstract, enigmatic, or transcendent.